A Study on Correlation of Serum IGE Levels with Diagnosis and Management of Bronchial Asthma in Children - Hafiz Muhammad Huzaifah Shahid, Hafiz Muhammad Atif, Haseeb Amjad, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Traditional methods for identifying atopic individuals in allergy and respiratory illness studies include the responsiveness of allergy skin tests, serum IgE levels, and peripheral blood eosinophilia. Objectives: The main objective of the study is to find the association between Raised Serum IgE levels and bronchial asthma in children. Material and methods: This cross sectional study was conducted in Mayo Hospital Lahore during May 2021 till November 2021. The data was collected from 140 patients of age range 2 to 12 years. The doctor conducted a thorough examination of each patient, after which the required paperwork was completed. Results: 140 patients provided the data for this study. Gender, a family history of asthma, breastfeeding exclusively for the first six months, or living in a residential setting were not shown to have a significant impact on the amount of total serum IgE. Higher total serum IgE levels in asthmatics and older age groups, cigarette smoke exposure, and higher eosinophil counts are correlated. Asthmatics had higher IgE levels. Conclusion: It is concluded that there is a correlation between total serum IgE levels and a child's propensity for wheeze and early sensitivity to local aeroallergens. Allergy in children can be accurately predicted by measuring the serum total IgE level.